2021
DOI: 10.1016/j.ymthe.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

mRNA-encoded, constitutively active STINGV155M is a potent genetic adjuvant of antigen-specific CD8+ T cell response

Abstract: mRNA vaccines induce potent immune responses in preclinical models and clinical studies. Adjuvants are used to stimulate specific components of the immune system to increase immunogenicity of vaccines. We utilized a constitutively active mutation (V155M) of the stimulator of interferon (IFN) genes (STING), which had been described in a patient with STING-associated vasculopathy with onset in infancy (SAVI), to act as a genetic adjuvant for use with our lipid nanoparticle (LNP)-encapsulated mRNA vaccines. mRNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 71 publications
1
43
0
Order By: Relevance
“…To further improve vaccine efficacy, APC uptake and T cell activation can be optimized; for example, mannose-modified lipid nanoparticle–mRNA formulations are preferentially taken up by dendritic cells 150 , 201 , 202 . The efficacy of cancer vaccines can also be boosted by co-delivery of antigen mRNA with adjuvants 32 , 63 , 94 , 203 206 , co-stimulatory molecules 148 , 150 , 207 , 208 and immune checkpoint inhibitors 200 202 , 209 211 .…”
Section: Preclinical Studies and Clinical Trialsmentioning
confidence: 99%
“…To further improve vaccine efficacy, APC uptake and T cell activation can be optimized; for example, mannose-modified lipid nanoparticle–mRNA formulations are preferentially taken up by dendritic cells 150 , 201 , 202 . The efficacy of cancer vaccines can also be boosted by co-delivery of antigen mRNA with adjuvants 32 , 63 , 94 , 203 206 , co-stimulatory molecules 148 , 150 , 207 , 208 and immune checkpoint inhibitors 200 202 , 209 211 .…”
Section: Preclinical Studies and Clinical Trialsmentioning
confidence: 99%
“…reported a structurally active mutation (V155M) of the interferon (IFN) gene stimulator (STING) as a genetic adjuvant for a lipid nanoparticle coated mRNA vaccine. [ 52 ] The result showed that it was effective in promoting CD8 + T cell responses (Figure 2a).…”
Section: The Types Of Adjuvantsmentioning
confidence: 99%
“…Reproduced with permission. [ 52 ] Copyright 2021, Cell Press. b) Simplified diagram of the response to CpG ODNs.…”
Section: The Types Of Adjuvantsmentioning
confidence: 99%
“…[54] Omomyc effectively enhanced the cell penetration of CP-STING ~TM + cGAMP, resulting in higher level of CXCL10 secretion in dendritic cells and STING-impaired tumor cells compared with STING ~TM + cGAMP. Apart from these studies, another work needs to be mentioned is that a mRNA-encoded STING V155M mutant was developed as a genetic adjuvant by Huang et al [55] STING V155M is constitutively active with no need of agonist stimulation, [45] Reproduced with permission from Ref. 5.…”
Section: Protein-based Strategiesmentioning
confidence: 99%